Tata bahasa Jawa - Purwadi, 1971-; Mahmudi; Setijaningrum, Erna, 1970- (Yogyakarta : Media Abadi, 2005)
Javanese grammar
Daftar pustaka : p. 632-634
Keywords: Indonesian language -- Morphology -- History and criticism; Indonesian language -- Grammar -- History and criticism; Indonesian language -- Usage -- History and criticism